Defining Arabism: the Contestation of Arab Identity in the Hadrami Community in Betawi (History Department, Semarang State University and Historian Society of Indonesia, 2019)
This study of defining Arabism aims to analyze Arab identity in the hadrami community in Betawi. Arab identity in the hadrami community in Betawi could be seen in the use of the marriage title, and their respect for the ‘alawiyyin community. The hadrami community in Betawi made religion a distinctive feature of Arab identity, thus causing conflict between the hadrami community in defining Arabism. The problem in this study is events that occurred in the past, thus materials such as archives, books, journals, and newspapers related to the theme were used as sources in this study. The analysis of this study uses the hermeneutic phenomenology method in order to obtain a reconstruction of the history of Arabism that is close to the truth. This study provides the conclusion that identity is a source of conflict, resulting contestation in the hadrami community in Betawi. Kajian tentang mendefinisikan arabisme ini bertujuan untuk menganalisis identitas Arab pada komunitas hadrami di Betawi. Identitas Arab pada komunitas hadrami di Betawi dapat dilihat pada pemakaian gelar pernikahan, dan penghormatan mereka terhadap kelompok ‘alawiyyin. Komunitas hadrami di Betawi menjadikan agama sebagai bahan dari identitas Arab, sehingga menyebabkan konflik diantara komunitas hadrami untuk mendefinisikan arabisme pada identitas Arab tersebut. Masalah pada penelitian ini adalah segala peristiwa yang telah terjadi di masa lampau, maka bahan-bahan seperti arsip, buku, jurnal, dan surat kabar yang terkait dengan tema digunakan sebagai sumber dalam penelitian ini. Analisis penelitian ini menggunakan metode fenomenologi hermeneutik agar dapat diperoleh rekonstruksi sejarah arabisme yang mendekati dengan kebenaran. Penelitian ini memberikan kesimpulan bahwa identitas adalah sumber konflik sehingga menimbulkan kontestasi pada komunitas hadrami di Betawi.